Mursyid Perempuan: Studi Tentang Peran Nyai Thabibah dalam Tarekat Naqsyabandiyah Muzhariyah - Hafifuddin (Magister’s Program in Islamic Education Postgraduate Program, Universitas Annuqayah Sumenep, 2022)
This paper aims to determine the roles and impacts of the leaders (mursyid) of the Naqsyabandiyah Muzhariyah Tarekat coming from among women, especially in Madura. Within this congregation, there are several women who are its leaders (mursyidah). One of them is Nyai Thabibah bint Kiai Khudzaifah, Caretaker of the al-Bustan Girls Islamic Boarding School, Pamekasan. The research results show that Nyai Thabibah has a role in the religious and social fields. The impact of the Naqshbandiyah Muzhariyah Tarekat is tazkiyah an-nafs for all Muslim sisters because of entering the tarekat, they feel more comfortable, enthusiastic and fond of worship and doing good deeds such as istiqamah in sunnah prayers, do not feel better than other people, are more willing to give alms, ta'zhim towards teachers, love NU, etc.